1992
DOI: 10.1016/0014-5793(92)80540-w
|View full text |Cite
|
Sign up to set email alerts
|

Lipid domain reorganization and receptor events Results obtained with new fluorescent lipid probes

Abstract: Binding of a ligand to the extracellular site of a membrane receptor involves conformational changes not only of the extracellular and cytoplasmic sites but also of the membrane-spanning segments of the receptor protein. The lipids forming the environment of the trans-membrane receptor segments, being flexible and mobile, must follow the shape changes of the receptor molecule to some extent. For this reason ligandreceptor binding itself can be expected to result in changes of the packing of lipid molecules sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…22,47 The percolation threshold, which is defined as the switching point between the phases forming the connected and disconnected phase, has been proposed to possess functional significance for biological inplane bimolecular reactions and the aggregation of protein subunits to form a functioning protein complex. 20,48,49 Even though a large number of experimental studies have focused on the lipid bilayer properties within the two-phase region, a proper understanding of the thermodynamic and dynamic behavior of such lipid bilayer systems is still lacking. 5 Our findings suggest that the lateral membrane structure within the gel-fluid coexistence region can exist as a nonequilibrium long-living complex heterogeneous structure composed of coexisting gel and fluid domains characterized by a lifetime on the order of hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,47 The percolation threshold, which is defined as the switching point between the phases forming the connected and disconnected phase, has been proposed to possess functional significance for biological inplane bimolecular reactions and the aggregation of protein subunits to form a functioning protein complex. 20,48,49 Even though a large number of experimental studies have focused on the lipid bilayer properties within the two-phase region, a proper understanding of the thermodynamic and dynamic behavior of such lipid bilayer systems is still lacking. 5 Our findings suggest that the lateral membrane structure within the gel-fluid coexistence region can exist as a nonequilibrium long-living complex heterogeneous structure composed of coexisting gel and fluid domains characterized by a lifetime on the order of hours.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral organization of two-component lipid bilayers within the phase separated regions has been investigated by a number of techniques such as ESR and FRAP, which clearly have demonstrated that the two-phase region can be characterized as a heterogeneous percolative-like structure. , The percolation threshold, which is defined as the switching point between the phases forming the connected and disconnected phase, has been proposed to possess functional significance for biological inplane bimolecular reactions and the aggregation of protein subunits to form a functioning protein complex. ,, Even though a large number of experimental studies have focused on the lipid bilayer properties within the two-phase region, a proper understanding of the thermodynamic and dynamic behavior of such lipid bilayer systems is still lacking …”
Section: Discussionmentioning
confidence: 99%